Macroeconomic, Political and Institutional Factors of Economic Growth - O. Zhorayev; H. He (Экономика: стратегия и практика)
Broad theoretical and empirical literature discusses how economic development is affected by different economic, political, institutional, social, and other factors. The classic macroeconomic growth theory argues that poorer states must have higher rates of economic growth compared to more prosperous states due to the so-called ‘catch-up effect’. The concept of ‘institutional sclerosis’, suggested by Olson, claims that economic performance is worse in countries that have powerful interest groups. Some scholars suggest that economic growth is conditioned by ‘institutional coherence’ when one institution in a country promotes the efficiency of another. In this research, using regression analysis we estimate the effect of different factors on economic growth in 187 countries from 2001 to 2018. Our findings do not fully support Olson’s argument that economic decline in some countries was conditioned by the influence of interest groups. Our econometric results do not confirm the importance of the effectiveness of state governance and the quality of public policy. At the same time, the most robust result of our analysis is a statistically significant negative relationship between the level of a country’s initial economic development and its following medium- and long-term economic growth. This research contributes to the existing literature by testing Olson’s institutional sclerosis effect for the last two decade,; estimating the combined effect of interacted variables that explains predictions of both ‘interest groups’ and ‘varieties of capitalism’ theories; considering various macroeconomic and social factors along with political ones in one multivariate model.